Implementasi Peningkatan Produktivitas Perusahaan dengan Metode American Productivity Center pada UD. XY - Marcy Lolita Pattiapon; Nil Edwin Maitimu (Industrial Engineering Study Program, Pattimura University, 2024)
The company's main goal is to achieve maximum profits. To achieve this goal, the company carries out its business operations. Operational processes are carried out by paying attention to productivity levels. Productivity plays an important role for companies in facing intense business competition, so every company is required to improve its performance in order to compete with other competitors. UD. XY is an industry that focuses on the furniture sector and produces household furniture. The problem faced by the company was UD's inability. To evaluate the level of productivity that has been achieved in previous years. This research aims to identify productivity UD. XY and analyze changes in the input used by the company, so that it can determine the input aspects that require improvement to increase productivity. The approach used to analyze productivity levels is through the American Productivity Center (APC) method, which allows comparisons between the value of input issued and the output obtained. The research results show a decline in productivity, where the productivity index was recorded to have fallen by -1.7% in 2022, -3.2% in 2023, and -2.1% in 2023. This decline was caused by the company's internal problems, namely inefficiency in the use of resources which ends in increased production costs. In 2023, even though the output value reached IDR 3,219,000,000, productivity still decreased by -2.0%, so the company experienced a loss in resource utilization which reached IDR 64,380,000 in 2023.